2021
DOI: 10.1212/wnl.0000000000012801
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: Purpose of the ReviewThis article reviews recent breakthroughs in the treatment of acute ischemic stroke, mainly focusing on the evolution of endovascular thrombectomy, its impact on guidelines, and the need for and implications of next-generation randomized controlled trials.Recent FindingsEndovascular thrombectomy is a powerful tool to treat large vessel occlusion strokes and multiple trials over the past 5 years have established its safety and efficacy in the treatment of anterior circulation large vessel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 67 publications
3
72
1
4
Order By: Relevance
“…However, there has been less focus on the sub-acute and chronic phases of rehabilitative training programs that have been designed for the speedy recovery of the neurological and daily life activities of patients. Reviewing the current literature, it is possible to notice how the inclusion and exclusion criteria of aggressive intervention therapy namely, intravenous thrombolytic and/or intra-arterial (IA) thrombectomy treatments (3)(4)(5), and the cardiogenic origin induced index stroke episode have not been thoroughly investigated, as well as the long-term outcome for this type of stroke patients. For most patients with stroke and…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been less focus on the sub-acute and chronic phases of rehabilitative training programs that have been designed for the speedy recovery of the neurological and daily life activities of patients. Reviewing the current literature, it is possible to notice how the inclusion and exclusion criteria of aggressive intervention therapy namely, intravenous thrombolytic and/or intra-arterial (IA) thrombectomy treatments (3)(4)(5), and the cardiogenic origin induced index stroke episode have not been thoroughly investigated, as well as the long-term outcome for this type of stroke patients. For most patients with stroke and…”
Section: Discussionmentioning
confidence: 99%
“…Successful EVT leads to significantly improved clinical outcomes for emergent LVO stroke and several studies have demonstrated its efficacy beyond the strict RCT inclusion criteria. 11 , 12 However, in the context of limited resources, substantial procedural costs, globally increasing stroke cases, and the socioeconomic costs of healthcare selecting those patients likely to benefit from EVT is of increasing importance. In the setting of patient selection and prognostication for good EVT outcome, age is an important variable.…”
Section: Discussionmentioning
confidence: 99%
“…IVT is an established part of stroke reperfusion therapy that, in the setting of large vessel occlusions (LVO), should be combined with mechanical reperfusion [10][11][12][13][14][15][16]. There is some evidence in intracranial LVO strokes that IVT administration prior to emergency mechanical reperfusion (EMR) may be associated with increased early recanalization rate [14][15][16]; but this may be less applicable to AIS-CA due to the typically large thrombus burden in AIS-CA [6,9,17]. Some authors suggest that the bleeding risk with mechanical recanalization may be increased if IVT precedes mechanical thrombectomy (MT) [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Pivotal trials of mechanical intervention in AIS have been focused on intracranial LVO; patients with AIS due to extracranial carotid artery (CA) occlusion were routinely excluded or severely underrepresented [ 17 , 19 , 20 ]. As a result of trials, MT of the intracranial CA occlusion causing AIS is today recommended in all eligible patients (class I, level of evidence A recommendation) [ 12 , 17 ]. This contrasts with the data gap regarding EMR of causative occlusions of the extracranial internal CA, including tandem lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation